The Influence of Liquidity, Profitability, Leverage, and Economic Value Added on Stock Returns (Empirical Study on Basic and Chemical Industry Sector Manufacturing Companies Listed on the IDX in 2020-2022) - Ilham Maulana Pribadi; Nursiam Nursiam (ITB AAS INDONESIA, 2024)
This research aims to investigate how liquidity, profitability, leverage, and economic value added influence stock returns in manufacturing firms in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative methodology, concentrating on manufacturing firms within the basic industry and chemical sectors that are listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The study utilizes purposive sampling, a technique for selecting samples based on specific predetermined criteria, yielding 85 samples. The gathered data were evaluated utilizing SPSS software through descriptive statistics and multiple regression analysis. This study found that overall, all independent variables (liquidity, profitability, leverage, and economic value added) impact stock returns. However, partial analysis shows that liquidity and economic value added do not influence stock returns. Conversely, profitability and leverage are proven to affect stock returns.